Negative allosteric modulators of the human calcium‐sensing receptor bind to overlapping and distinct sites within the 7‐transmembrane domain. (12th February 2020) - Josephs, Tracy M.; Keller, Andrew N.; Khajehali, Elham; DeBono, Aaron; Langmead, Christopher J.; Conigrave, Arthur D.; Capuano, Ben; Kufareva, Irina; Gregory, Karen J.; Leach, Katie
Abstract : Background and Purpose: Negative allosteric modulators (NAMs) that target the calcium‐sensing receptor (CaS receptor) were originally developed for the treatment of osteoporosis by stimulating the release of endogenous parathyroid hormone, but failed in human clinical trials. Several chemically and structurally distinct NAM scaffolds have been described, but it is not known how these different scaffolds interact with the CaS receptor to inhibit receptor signalling in response to agonists. Experimental Approach: In the present study, we used a mutagenesis approach combined with analytical pharmacology and computational modelling to probe the binding sites of four distinct NAM scaffolds. Key Results: Although all four scaffolds bind to the 7‐transmembrane and/or extracellular or intracellular loops, they occupy distinct regions, as previously shown for positive allosteric modulators of the CaS receptor. Furthermore, different NAM scaffolds mediate negative allosteric modulation via distinct amino acid networks. Conclusion and Implications: These findings aid our understanding of how different NAMs bind to and inhibit the CaS receptor. Elucidation of allosteric binding sites in the CaS receptor has implications for the discovery of novel allosteric modulators. Abstract :